2011
DOI: 10.1002/bapi.201110794
|View full text |Cite
|
Sign up to set email alerts
|

Ermittlung ausgewählter mechanischer Kennwerte thermisch modifizierter Buche

Abstract: Untersuchungen zu physikalisch‐mechanischen und chemischen Eigenschaften thermisch modifizierten Holzes sind bereits seit den frühen 1950er Jahren durchgeführt und wieder verstärkt in den letzten zehn bis zwanzig Jahren aufgenommen worden. Generelle Zusammenhänge zwischen den Behandlungsparametern und den Eigenschaften des vergüteten Holzes sind weitgehend bekannt. Gegenstand und Ziel der vorliegenden Untersuchungen war die Ermittlung ausgewählter mechanischer Kennwerte von im Autoklaven nach zwei unterschiedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…The results of this study reveal that Young’s moduli obtained from tension were higher than those from compression tests for reference and thermally treated beech and birch. This trend is similar to that obtained by Wetzig et al 36 , where greater E L values from tensile than compression tests were obtained for heat-treated and untreated beech. This tension–compression asymmetry of wood elastic properties was also noticed for untreated beech 37 and for untreated walnut and cherry wood 38 , 39 .…”
Section: Quasi-static Tests Results and Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of this study reveal that Young’s moduli obtained from tension were higher than those from compression tests for reference and thermally treated beech and birch. This trend is similar to that obtained by Wetzig et al 36 , where greater E L values from tensile than compression tests were obtained for heat-treated and untreated beech. This tension–compression asymmetry of wood elastic properties was also noticed for untreated beech 37 and for untreated walnut and cherry wood 38 , 39 .…”
Section: Quasi-static Tests Results and Discussionsupporting
confidence: 91%
“…Overall, the Young's moduli from ultrasonic tests have higher values than those obtained from quasi-static tests in all directions. This general tendency is well documented in the literature 36,41,42 . This difference, however, is more noticeable in the radial direction (up to 75% and 107% higher values obtained by ultrasound for beech and birch, respectively).…”
Section: Ultrasonic Characterisation: Results and Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…When Missanjo and Matsumura (2016) studied the relationship between wood density and mechanical properties, they found that wood density had a significant positive correlation with bending strength. In addition, Wetzig et al (2011) reported that wood density had an important effect on tensile strength, and the strength was increased with the increase of density. Therefore, the change in tensile strength and bending strength of pine wood after extraction was mainly caused by the change of density.…”
Section: Analysis Of the Influence Of Extractive On The Mechanical Properties Of Pine Woodmentioning
confidence: 99%